Therapeutic Applications of Ethanol: A Review - Brendan Le Daré; Thomas Gicquel (Frontiers Media S.A., 2019)
Purpose: To review knowledge on therapeutic uses of ethanol and the latter's effectiveness and safety profiles in a range of indications. Methods: MEDLINE and PubMed databases were searched for relevant peer-reviewed papers published in English between 1888 and 2018 using the following search terms: ethanol, therapeutic, alcohol withdrawal syndrome, antiseptic, antidote, methanol, ethylene glycol, neurolysis, embolization, cyst, sclerosing agent, sclerotherapy, arteriovenous malformations, ablating agent. Studies providing information about association between alcohol and therapeutic indications, or mechanic explanation for the association were included for review. Results: According to the World Health Organization, approximately three millions deaths worldwide are attributable to alcohol consumption each year. However, the low-to-moderate consumption of ethanol has a number of beneficial effects (mainly on cardiovascular mortality and diabetes). Hence, ethanol has an unusual spectrum of effects that seems interesting for therapeutic purposes. Ethanol's risk-benefit ratio appears to be positive in some therapeutic indications such as antidote to methanol or ethylene glycol poisoning, neurolysis, alcohol withdrawal syndrome, or antiseptic. Conclusion: With the development of interventional radio technologies, and thus extremely precise access to anatomical structures, alcohol has been given new indications - particularly as an embolization, sclerosing or ablation agent. Moreover, constant progress in our knowledge of ethanol's pharmacodynamics might highlight other therapeutic indications for this compound in the future. Ethanol's low cost and wide availability make it a valuable therapeutic agent, compared with other reference treatments. Furthermore, ethanol has a long track record of safety and effectiveness in the indications mentioned above.